Developing Educators Of Strong Character Through Pancasila Courses For Elementary School Teacher Education Students - Nurhudayana Ridwan; Sulfasyah; Jumiati Nur (Indonesian Journal of Pedagogy and Teacher Education, 2024)
The aim of this community service activity is to enhance the understanding and application of Pancasila values among Elementary School Teacher Education (PGSD) students through the Pancasila course as an ethical system. The background of this activity arises from the need for a more practical and contextual approach to character education. The implementation method involves online group discussions with 21 prospective elementary school teachers. The findings indicate that approximately 80% of students have achieved a good level of understanding of Pancasila ethical concepts, with 85% actively participating in group discussions. A significant number of groups, around 75%, engaged in in-depth discussions and effective collaboration regarding the application of Pancasila values in daily life and educational environments. Good analytical skills were demonstrated by about 78% of students in detailing and applying Pancasila values to case studies. From this activity, students can provide significant benefits to society through improved character education. The conclusion of this activity emphasizes theoretical contributions to character education through the Pancasila course and suggests improvements such as increased use of technology, provision of more structured teaching materials, regular evaluations, and involvement of external stakeholders in future community service activities. Thus, this activity makes a positive contribution to shaping the character of PGSD students and strengthening community involvement in the learning process.